Fracture Characterization of Lower Cambrian Niutitang Shale in Cen’gong Block, Southern China - Wang, Xinghua; Wang, Ruyue; Guo, Rongtao; Dahi Taleghani, Arash; Su, Shuaitao; Ding, Wenlong; Gong, Yue; Lai, Fuqiang; Wu, Zhonghu; Su, Yushan; Cao, Zhe (Frontiers in Earth Science, 2022)
The marine shale of southern China is characterized by old sedimentary formations, multiple tectonic activities, and poor preservation conditions. The fracture system in this shale reservoir is extraordinarily complex, greatly adding to difficulties for shale gas exploration and development. Based on field surveys, drilling cores, seismic data interpretation, and experimental tests, we try to characterize the developmental characteristics of shale fractures at different scales and delineate the stages of fractures in the Cen’gong block. The results show that the Cen’gong block is a saddle-shaped structure formed by the northeast-oriented Banxi anticline and the southwest-oriented Lannigan anticline. There are four types of core fractures developed in the study area, namely, pyrite-filled fractures, fibrous veins, subvertical fractures, and slip fractures, and the forming time of these fractures are later in turn based on the intersecting relationships and analysis of filling minerals. The fracture rose diagram and the paleomagnetic orientation experiments indicate that the fracture direction is mainly NNE and partly NW, consistent with the direction of faults identified in the seismic data. Quantitative statistics have been conducted for fracture aperture, length, and density distribution. The fracture abundance has a close relationship with buried depth and regional faults in the study area.